Lanskap Linguistik dari Penamaan Ruang Terbuka di Pantai Indah Kapuk - Cecilia Dhea Odhilia; Sonya Ayu Kumala (e-LinguaTera, 2025)
The observation of languages in public spaces, including signboards and written text, falls under the concept of linguistic landscape (LL). The research aims to analyze language patterns and uncover the meanings embedded in the names of these public spaces. By applying the principles of linguistic landscape theory (Landry and Bourhis, 1997), which examine how public language reflects social identities and dynamics. This research adopts a descriptive and qualitative approach to investigate the linguistic landscape of open space naming in Pantai Indah Kapuk. Data were collected through observations and interviews with several informants. The main objective is to identify language patterns using the Kamus Besar Bahasa Indonesia (KBBI) and the Oxford English Dictionary (OED). Furthermore, to explain the meanings of the names, the author analyzed the presuppositional meanings according to Nystroom: categorial, associative, and emotive. The author using the UCREL Semantic Analysis System (USAS) to decode categorical meanings, while associative and emotive meanings were derived from interview data. The results of this study are as follows: Analyzing the names of eight open spaces in PIK revealed the language pattern where English is the most dominantly used language. Additionally, the author identified eight categorical meaning, USAS categories Z2, W3, and M7 being the most dominant. The categorial meanings that emerge from the names of open spaces are related to geography, natural features, and specific locations based on USAS categories. Furthermore, the most common associative meaning is positive, highlighting the identity, culture, history, and environment of PIK. Finally, the emotive meanings found indicate positive emotions such as joy and satisfaction, reflecting the ability of these locations to leave a deep and lasting impression on visitors.